2021
DOI: 10.1111/hsc.13563
|View full text |Cite
|
Sign up to set email alerts
|

Arab Muslims' Perceptions of Perinatal Loss Care in the United States of America

Abstract: The purpose of this pilot study was to examine the perceptions and attitudes of immigrant Arab Muslims residing in the United States regarding psychosocial bereavement practices common in the United States after perinatal loss. In addition, we pilot tested an investigator-developed instrument for collecting data regarding culturally relevant psychosocial bereavement practices of Arab Muslims after perinatal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is important to discuss a family's specific desires that may divert from a traditional cultural expectation. One study found that Muslim families desired the same options typically provided as a part of Western bereavement care in addition to care options specific to their faith (Alaradi et al, 2022). As such, a combination of bereavement services that are developed in tandem with the family is ideal.…”
Section: Istock/edwin Tanmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to discuss a family's specific desires that may divert from a traditional cultural expectation. One study found that Muslim families desired the same options typically provided as a part of Western bereavement care in addition to care options specific to their faith (Alaradi et al, 2022). As such, a combination of bereavement services that are developed in tandem with the family is ideal.…”
Section: Istock/edwin Tanmentioning
confidence: 99%
“…It is important for nurses and other health care providers to understand the cultural context of perinatal loss and to provide culturally sensitive care to diverse families (Fernández et al, 2020). They should recognize typical psychosocial care provided in American hospitals after perinatal loss is based on Western cultures and may not be congruent with the desires of other cultures (Alaradi et al, 2022). Cultural beliefs and practices about perinatal loss vary among diverse groups.…”
Section: Cultural Beliefs Practices and Stigmamentioning
confidence: 99%
See 1 more Smart Citation